On the complexity of exact counting of dynamically irreducible polynomials. (July 2020) - Gómez-Pérez, Domingo; Mérai, László; Shparlinski, Igor E.
Abstract: We give an efficient algorithm to enumerate all sets of r ⩾ 1 quadratic polynomials over a finite field which remain irreducible under iterations and compositions.